Social Capital of Rice Farmers in Andhra Pradesh and Kerala: A Social Network Analysis - Suddamalla Manoj Kumar Reddy; Binoo P Bonny; Aparna Radhakrishnan; M Hema (Indian Journal of Extension Education, 2026)
The study explored the social capital among the rice farming communities, which is crucial in the context of climate change for building their resilience. The study was conducted in the South Indian states of Andhra Pradesh (AP) and Kerala during 2023. Primary data were collected from 120 farmers using a pretested schedule. Three social capital measures, viz., bonding capital, bridging capital, and linking capital, were analysed using social network analysis of the information sourcing and support networks of farmers. The results revealed relatively higher social capital among the farmers of Kerala than those of AP. Networks of both states had lower bonding capital, explained by lower density, moderate closeness centrality, and moderate modularity values. In the case of bridging and linking capital, Kerala regions had relatively higher levels than AP, explained by their in-degree centrality and betweenness centrality. The network maps also revealed greater reliance on input dealers for information in AP regions, whereas Kerala farmers relied on institutional sources. The results call for improving the bonding capital of all regions and the bridging and linking capital of AP farmers to expand their overall resilience.